Supramolecular‐mediated ball‐in‐ball porous carbon nanospheres for ultrafast energy storage. Issue 4 (12th December 2021) - Yao, Lei; Lin, Junsheng; Chen, Yuanyuan; Li, Xiujuan; Wang, Dongrui; Yang, Haitao; Deng, Libo; Zheng, Zijian
Abstract: Hierarchical porous carbons are the most viable electrode material for supercapacitors because of their balanced capacitive performance and chemical stability. Their pore connectivity plays a pivotal role in electrolyte transport, which is quantified by a new parameter, defined in this work as the longest possible pore separation (LPPS). Herein, we report hierarchical porous carbon nanospheres (HPC‐NS) with a unique ball‐in‐ball structure, which is achieved by the pyrolysis of a supramolecular complex of γ‐cyclodextrin (γ‐CD)/PEO‐PPO‐PEO (F127). This approach differs from the conventional soft‐templating method in that, apart from the assembly of the monomicelles that leads to the host nanospheres (approximately 300 nm), the γ‐CD‐containing monomicelles themselves are converted to small porous carbon nanospheres (<10 nm), which results in an ultralow LPPS of 10 nm, representing the best‐known pore connectivity of the HPC family. The HPC‐NS delivers a high specific capacitance (405 F g −1 at 1 A g −1 and 71% capacitance retention at 200 A g −1 ), wide voltage window (up to 1.6 V), and simultaneously high energy and power densities (24.3 Wh kg −1 at a power density of 151 W kg −1 and 9 Wh kg −1 at 10 5 W kg −1 ) in aqueous electrolytes. This new strategy boosts the development of porous carbon electrodes for aqueous supercapacitors with simultaneously high power and energy densities. Abstract : Highly oxygenated and hierarchical porous carbon nanospheres (HPC‐NS) were prepared by one‐pot carbonization and activation of supramolecular micelles formed from γ‐cyclodextrin and the amphiphilic block copolymer F127 inclusion complex. HPC‐NS delivers a high capacitance (405 F g −1 at 1 A g −1 ) and a wide voltage window (1.6 V) in an aqueous supercapacitor. The enabled device displays an energy density of 23.36 Wh kg −1 and retains a value of 9 Wh kg −1 even at an ultrahigh power density of 10 5 W kg −1 .